Optimalisasi Lembaga Keuangan Syariah Dalam Era Digital Untuk Memajukan Industri Teknologi Bagi Generasi Z - Maulydia Anggraini; Desy Safitri; Lidia Desiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In the rapidly developing digital era, Sharia Financial Institutions (LKS) have a great opportunity to innovate and adapt to modern technology to support economic growth, especially for Generation Z. This research aims to identify optimization steps that can be taken by LKS in facing transformation digital, as well as exploring the role of sharia financial technology (fintech) in advancing the technology industry. Generation Z, as a highly tech-savvy group, has different needs and preferences than previous generations. Therefore, LKS is required to integrate digital-based financial services that are in accordance with sharia principles, so that they can be more attractive and serve this segment. This research uses a qualitative approach with literature studies and in-depth interviews with industry practitioners. The research results show that collaboration between LKS and sharia fintech, development of inclusive digital platforms, and increasing sharia financial literacy among Generation Z are key factors in advancing the sharia technology industry. This optimization will not only increase the competitiveness of LKS, but also support the sustainable development of the sharia digital economy.